Development and validation of two SYBR green PCR assays and a multiplex real-time PCR for the detection of Shiga toxin-producing Escherichia coli in meat - Brusa, Victoria (2015)
Shiga toxin-producing Escherichia coli (STEC) are recognized as food-borne pathogens. We developed and validated two SYBR green PCR (SYBR-PCR) and a real-time multiplex PCR (RT-PCR) to detect stx1 and stx2 genes in meat samples, and compared these techniques in ground beef samples from retail stores. One set of primers and one hydrolysis probe were designed for each stx gene. For RT-PCR, an internal amplification control (IAC) was used. All PCR intra-laboratory validations were performed using pure strains and artificially contaminated ground beef samples. A total of 50 STEC and 30 non-STEC strains were used. Naturally contaminated ground beef samples (n = 103) were obtained from retail stores and screened with SYBR-PCR and RT-PCR, and stxpositive samples were processed for STEC isolation. In the intra-laboratory validation, each PCR obtained a 1 × 102 CFU mL−1 limit of detection and 100% inclusivity and exclusivity. The same results were obtained when different laboratory analysts in alternate days performed the assay. The level of agreement obtained with SYBR-PCR and RT-PCR was kappa = 0.758 and 0.801 (P b 0.001) for stx1 and stx2 gene detection, respectively. Two PCR strategies were developed and validated, and excellent performance with artificially contaminated ground beef samples was obtained. However, the efforts made to isolate STEC from retail store samples were not enough. Only 11 STEC strains were isolated from 35 stx-positive ground beef samples identically detected by all PCRs. The combination of molecular approaches based on the identification of a virulence genotypic profile of STEC must be considered to improve isolation.